DISHARMONISASI KEPALA DAERAH (ANALISIS FRAMING ROBERT N. ENTMAN PADA PEMBERITAAN MEDIA ONLINE ULASAN.CO) - Ella Afnira; Eki Darmawan; Ryan Anggria Pratama (LPPM Universitas Abdurrab, 2024)
This research aims to understand and analyze how the online media outlet Ulasan.co frames the news about the leadership of the Governor and Deputy Governor of the Riau Islands, where three months after their inauguration, they were hit by issues of disharmony. Ulasan.co is the most prominent online media platform in the Riau Islands that frequently highlights these issues. This study analyzes the news texts from Ulasan.co titled